Specialized movement on the rowing ergometer and post-workout changes in selected peripheral blood parameters - a case report - Proia, P.; Amato, A.; Contró, V.; Thiel, D.; Vostatková, P.; Buryta, B.; Kolbowicz, M.; Lewandowski, T.; Nowakowska, A. (Central European Journal of Sport Sciences and Medicine, 2018)
Rowing is a sport discipline, which requires extreme physical strength and endurance and appropriate aerobic and anaerobic capacity as well. However, when the workout intensity and load is very high, exercise is associated with temporary changes in cellular metabolism and the immune system. The study included one male rower aged 28 years - the highly-skilled and experienced athlete. We determined basic cardiorespiratory fitness measures, complete blood count, and 24 clinical chemistry parameters including relevant biochemical and haematological parameters and matrix metaloproteinases activities. Maximal exercise on the rowing ergometer induced 2-fold increase in absolute counts of all leukocytes subsets. There was observed an increase in C-reactive protein concentrations as well. MMP-9 activity increased 1,3-fold compared to the baseline value. Exhaustive exercise caused significant changes in creatinine and urea serum levels, but the most prominent changes were found in total and direct bilirubin concentrations. Maximal exercise induced also a decrease in the iron and magnesium levels. No changes in ALT, GGT and ALP activity were observed, while increase in CK, AST and LDH activity in post-exercise time and the decrease during the recovery was found. Therefore acute specialized movement on the rowing ergometer is not the cause of muscular damage, but rather indicate efficient adaptation to the physical exercise. Moreover, it seems that maximal exercise induces an inflammatory response characterized by greater count of all subpopulations of leukocytes, elevated levels of CRP and MMP-9 serum activity.